Audit Energi Pada Gedung Universitas Pertamina Menggunakan Metode AHP (Analytical Hierarchy Process) - Muhamad FE Nugroho; Wahyu Agung Pramudito; Soni Prayogi (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
This service aims to conduct an energy audit at the Pertamina University Building using the Analytical Hierarchy Process (AHP) method. This audit process involves identifying and analyzing energy consumption in various building facilities, as well as determining priorities for energy efficiency measures that can be implemented. The AHP method is used to facilitate decision making by comparing various criteria and alternative actions systematically and objectively. The audit results show that there are several areas with significant energy savings potential, such as lighting systems, air conditioning and the use of electrical equipment. The resulting recommendations include the implementation of energy-saving technology, optimizing equipment operations, as well as education and training for building users regarding energy-saving practices. Implementation of the results of this audit is expected to increase energy efficiency in the Pertamina University Building, reduce operational costs, and contribute to environmental conservation efforts.